Incorporating organizational innovation as a missing link in the examination of the EO-performance linkage - Zakaria, Nazlina; Abdullah, Nor Azimah Chew; Yusoff, Rushami Zien (2017)
Drawing from resource-based view (RBV), this study generally aimed to investigate the relationship between entrepreneurial orientation (EO), organizational innovation, and organizational performance.It also examined the mediating effect of organizational innovation on the relationship between EO and organizational performance.To achieve these objectives, data were gathered from the owners/managers of manufacturing SMEs in the west coast of Peninsular Malaysia.Of 531 questionnaires distributed, only 331 (60.5%) were analyzed PLS-SEM.Significance levels of 0.05 and 0.01 were used as the critical level for decision making on the hypotheses.All hypotheses on the direct and indirect relationships between the EO and organizational performance of SMEs was supported.The finding strongly supported the RBV theory when the main effect of EO and mediating effects of organizational innovation displayed significant change in the relationship.